2011
DOI: 10.1007/978-3-642-25243-3_30
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Finger-Knuckle-Print Based Recognition System Fusing SIFT and SURF Matching Scores

Abstract: Abstract. This paper presents a novel combination of local-local information for an efficient finger-knuckle-print (FKP) based recognition system which is robust to scale and rotation. The non-uniform brightness of the FKP due to relatively curvature surface is corrected and texture is enhanced. The local features of the enhanced FKP are extracted using the scale invariant feature transform (SIFT) and the speeded up robust features (SURF). Corresponding features of the enrolled and the query FKPs are matched u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…In order to evaluate the performance of our method, we apply the EER as benchmark in biometric systems. And in terms of feature matching technique, we choose the Speeded-Up Robust Features (SURF) [19] method.…”
Section: Methodsmentioning
confidence: 99%
“…In order to evaluate the performance of our method, we apply the EER as benchmark in biometric systems. And in terms of feature matching technique, we choose the Speeded-Up Robust Features (SURF) [19] method.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows a summary of researches on finger knuckle recognition. Most researches [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] focused on recognition algorithms for texture patterns of PIP joints and evaluated its performance using a public finger knuckle image database such as the PolyU FKP database [18]. The images in the PolyU FKP database are captured under the controlled conditions, since the subject puts his/her finger on fixed blocks in order to reduce the spatial variations and capture clear line features of a finger knuckle.…”
Section: Introductionmentioning
confidence: 99%
“…Effectiveness of such coding approaches have been demonstrated in iris recognition [20] and palmprint recognition [21]. Some researches [8][9][10] employed local feature descriptors such as SIFT and SURF, which are used in the field of computer vision. Another approach [5,12,15,17] employed BandLimited Phase-Only Correlation (BLPOC), which is an image matching technique using the phase components in 2D Discrete Fourier Transforms (2D DFTs) of given images [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the skin pattern on the finger-knuckle is highly rich in texture due to skin folds and creases, and hence, can be considered as a biometric identifier. Various advantages of using Finger Knuckle Print (FKP) include rich in texture features, easily accessible, contact-less image acquisition, invariant to emotions and other behavioral aspects such as tiredness, stable features and acceptability in the society [3]. Literature survey of related work has already been discussed in detail, in our earlier papers [11] [24].…”
Section: Introductionmentioning
confidence: 99%